IMPLEMENTASI PEMBELAJARAN TERPADU DI MI WAHID HASYIM 02 DAU KABUPATEN MALANG - Naufalita Shabrina Ramadhani; Ika Ratih Sulistiani; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research is based on how the constraints of implementing integrated learning in the classroom. There are still many students who are less active and understand integrated learning, and have not even been able to achieve good learning outcomes. This research was conducted at MI Wahid Hasyim 02 Dau Malang. The purpose of this study is to describe the planning, implementation, and constraints of learning activities that apply integrated learning. This research uses a case study approach. The data collection used is the method of observation, interviews, and documentation. In learning, teachers make various efforts in implementing integrated learning. The results showed that the teacher made a lesson plan in integrated learning, then for its implementation the teacher applied a suitable method to be used in learning. Keywords: Implementation, integrated learning